A Query on Identification, Classification and Synoptic Analysis of Heat Waves in Kerman Province - Yousef Ghavidel Rahimi; Mohammad Rezaei (نشریه جغرافیا و برنامه‌ریزی, 2016)
Heat waves are considered as one of the important climatic hazards in the world and especially in Iran and it seems that, due to intensification of global warming, their occurrence has increased in recent years than in the past. This study has paid attention to quality and quantity evaluation and synoptic analysis of heat waves in the KermanProvince. For this purpose, At first, the daily maximum temperature data, in month of July (as the warmest month in the year) was put in a statistical period of 24-years (1986-2009) from meteorological organization, for 4 synoptic stations of Kerman, Bam, Anar and Sirjan. In order to classify heat waves, standardized temperature data and on its basis, anomalies of 0 to 0.75 as a heat wave, 0.75 to 1.5 as severe heat waves, and greater than 1.5 were determined as super heat wave. The threshold values of 43.1, 42.1 and 41.2° C were calculated for all stations, respectively as threshold of heat wave, severe heat wave, and super heat wave and its continuity were considered at least for two days. Accordingly, During Statistical period of study, it was found 7 heat waves, which were, identified within 3 severe heat waves, and 1 super heat wave. Super heat wave in July 1998, was selected For the Synoptic analysis. This three-day wave, with an average temperature of 43/11° C, has been the most severe heat wave in KermanProvince. Results of synoptic analysis of super heat wave indicated that the establishment of Ganges low pressure on the ground and the domination of subtropical high-pressure of azores in high levels and also, high thickness atmosphere on the study area caused the subsidence of warm air and excessive heating of earth's surface, and created them mentioned super heat wave.